Rhythm Samaa - Mazaher Mosffa (مطالعات زبانی و بلاغی)
Rhythm, in Molana's great poetical sonnets, is one of the outstanding stylistic points in Molana's rhetoric and musical poems. His affinity with music and Samaa and his mystical appreciation of human internal Samaa as well as that in universe, resulted in such a variety in meters. The present text which is on meter and versification variety and its beauty and appropriateness with Molana's circumstances in Shams' sonnets, has been taken from Dr. Mazaher Mosaffa's lecture on Molana Commemoration in central library of Tehran University in 25 Dec. 1973. The lecture, along with 7 tables of sonnets' meters, was previously published in Rahnamaye Ketab (1975, Vols. 7-9) which truly witnesses his poetic dexterity on Farsi and Arabic versifications. To commemorate the most eminent prose and sonnet poet of our time, and with Dr. Amirbano Karimi Firouzkohi (Mosafa)'s attempt, a part of that valuable lecture is granted to be published here with no change.